TOP2A deficiency leads to human recurrent spontaneous abortion and growth retardation of mouse pre-implantation embryos - Yuhan Duan; Huijia Fu; Jiayu Huang; Nanlin Yin; Linhong Liu; Xiru Liu (BMC, 2022)
Abstract Background Recurrent spontaneous abortion (RSA), is a dangerous pregnancy-related condition and is a subject of debate in the gynaecology and obstetrics communities. The objective of this study was to determine the function of DNA Topoisomerase II Alpha (TOP2A) in RSA and elucidate the underlying molecular mechanisms. Methods In vitro models of TOP2A-knockdown and -overexpression were generated by transfecting specific sh-RNA lentivirus and overexpression plasmid, respectively. An in vitro TOP2A inhibition model was established by culturing mouse embryos at the two-cell stage in a medium containing PluriSIn2, a TOP2A inhibitor. Immunohistochemical staining was used to analyse expression of TOP2A in villi tissues of patients with RSA. Western blotting and qRT-PCR were used to analyse the expression of TOP2A and proteins involved in trophoblast functions, the FOXO signalling pathway, and the development of pre-implantation embryos. 5-Ethynyl-2'-deoxyuridine staining, TUNEL assay and flow cytometry were used to further evaluate the effect of TOP2A on cell proliferation and apoptosis. Transwell and wound healing assays were used to evaluate migration and invasion. Moreover, the effect of TOP2A inhibitor on embryos was determined by immunofluorescence and mitochondrial-related dyes. Results Evaluation of clinical samples revealed that the villi tissues of patients that have experienced RSA had lower TOP2A expression compared with that from women who have experienced normal pregnancy (P < 0.01). In vitro, TOP2A knockdown decreased the proliferation, migration, and invasion of trophoblast cell lines, and increased apoptosis and activation of the FOXO signalling pathway (P < 0.05). Conversely, TOP2A overexpression reversed these effects. Moreover, in vivo experiments confirmed that inhibition of TOP2A impairs trophectoderm differentiation, embryonic mitochondrial function as well as the developmental rate; however, no differences were noted in the expression of zygotic genome activation-related genes. Conclusions Collectively, our data suggest that lower TOP2A expression is related to RSA as it inhibits trophoblast cell proliferation, migration, and invasion by activation of the FOXO signalling pathway. Additionally, TOP2A inhibition resulted in impaired development of pre-implantation embryos in mice, which could be attributed to excessive oxidative stress. Graphical Abstract